Analysis in audit (Journal of Economic Research & Business Administration, 2016)
In the current economic conditions the main goal of any organization is efficient manner available financial and other resources for the implementation of effective activities that generate the desired result - a profit. At the same time managing the organization to make the right decisions and effective, it is important to determine the reserves growth efficiency of businesses, growth factors, profits, reduce losses. These and other objects performs financial analysis is an assessment of the financial statements in order to identify weaknesses in the financial position of the organization and improve its existing reserves. Outsourcing allows auditors to achieve greater objectivity of the results of the analysis. In recent years, services of auditors for the financial analysis are in high demand. First of all, it is connected with the desire of management to obtain reliable, objective, impartial assessment of the company. Thus, the study of financial analysis as audit-related services, is currently very topical.
Keywords: Audit; analysis; financial analysis; financial statements; comparison.